Serum exosomal microRNA‐766‐3p expression is associated with poor prognosis of esophageal squamous cell carcinoma - Liu, Shuang (Cancer Sci, 2020)
The aim was to analyze the association between exosomal microRNA (miR)‐766‐3p expression levels in serum and the prognosis of esophageal squamous cell carcinoma (ESCC). The serum global exosomal miRNA expression of ESCC patients was measured by microRNA microarray. Quantitative real‐time PCR was used to analyze the expression levels of candidate miRNAs in both serum and tissues from ESCC patients. Wilcoxon tests were applied to evaluate clinical characteristics and their association with serum levels of exosomal miR‐766‐3p. A Cox regression model was used to identify prognostic factors. The effects of miR‐766‐3p expression on cell migration and invasion were examined using Transwell assays, and CCK‐8 assays were carried out to measure cell proliferation. The TNM stage was associated with high serum exosomal miR‐766‐3p levels of ESCC patients (P = .030). Higher serum exosomal miR‐766‐3p expression levels were associated with poor prognosis (for overall survival, hazard ratio [HR] [95% confidence interval (CI)], 2.21 [1.00, 4.87]; for disease‐free survival, HR [95% CI], 2.15 [1.01, 4.59]). However, we found no association between the expression of miR‐766‐3p in tissue and ESCC prognosis. In vitro results showed that miR‐766‐3p promotes cell migration and invasion, but not cell proliferation. By using dual‐luciferase reporter assay, HOXA13 was confirmed as a direct target gene of miR‐766‐3p. The ESCC patients with highly expressed serum exosomal miR‐766‐3p had a significantly worse survival. Therefore, serum exosomal miR‐766‐3p could serve as a prognostic marker for the assessment of ESCC.